2003
DOI: 10.1107/s0108768102019894
|View full text |Cite
|
Sign up to set email alerts
|

Structural derivation and crystal chemistry of apatites

Abstract: The crystal structures of the [A(1)(2)][A(2)(3)](BO(4))(3)X apatites and the related compounds [A(1)(2)][A(2)(3)](BO(5))(3)X and [A(1)(2)][A(2)(3)](BO(3))(3)X are collated and reviewed. The structural aristotype for this family is Mn(5)Si(3) (D8(8) type, P6(3)/mcm symmetry), whose cation array approximates that of all derivatives and from which related structures arise through the systematic insertion of anions into tetrahedral, triangular or linear interstices. The construction of a hierarchy of space-groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
287
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(308 citation statements)
references
References 48 publications
11
287
1
9
Order By: Relevance
“…[9] Expansion of the average size of (As,P)O 4 tetrahedra is also reflected in the widely considered metaprism twist angle, giving the rotation of the two triangular faces formed by O1 and O2 about Ca1. [30] The trend of increasing twist with increasing As content up to As fraction 0.66 is consistent with the distortion between the (As,P)-O distances, where the (As,P)-O1 distance increases more rapidly than the (As,P)-O2 distance over the intermediate concentration range, which would serve to accentuate the metaprism twist in this same range. [9] This distortion or twist could result in the increasing of 1200 1000 800…”
Section: Evolution Of Aqueous Compositionsupporting
confidence: 61%
“…[9] Expansion of the average size of (As,P)O 4 tetrahedra is also reflected in the widely considered metaprism twist angle, giving the rotation of the two triangular faces formed by O1 and O2 about Ca1. [30] The trend of increasing twist with increasing As content up to As fraction 0.66 is consistent with the distortion between the (As,P)-O distances, where the (As,P)-O1 distance increases more rapidly than the (As,P)-O2 distance over the intermediate concentration range, which would serve to accentuate the metaprism twist in this same range. [9] This distortion or twist could result in the increasing of 1200 1000 800…”
Section: Evolution Of Aqueous Compositionsupporting
confidence: 61%
“…The triclinic distortion has been attributed to a size mismatch between the La3.33+2x/3(GeO4)6 framework and the La6O2 channels leading to underbonding at the channel La atoms, which is relieved by the triclinic distortion, through twisting of the GeO4 tetrahedra [20,21,39]. In prior work, we have shown that Y can be selectively doped into the La sites within the La3.33+2x/3(GeO4)6 framework altering the diameter, and hence relieving the triclinic distortion [18,37].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the crystal structure of HA is well described elsewhere (Elliott 1994;White and Dong 2003;Mathew and Takagi 2001), the detailed analysis of the electronic structure, bonding, charge transfer, optical and elastic properties is also available Rulis et al 2004;Snyders et al 2007;Ching et al 2009), while the readers interested in Posner's clusters are referred to still other papers (Treboux et al 2000;Kanzaki et al 2001). A shell model was developed to study the lattice dynamics of HA (Calderin et al 2005), while a cluster growth model was created to illustrate its growth (Onuma and Ito 1998).…”
Section: Ha (Or Hap or Ohap)mentioning
confidence: 99%
“…An anhydrous phase diagram CaO-P 2 O 5 at temperatures within 200-2200°C is shown in Fig. 3 (Kreidler and Hummel 1967;Carayon and Lacout 2003). Table 4 comprises crystallographic data of the existing CaPO 4 (Elliott 1994;White and Dong 2003;Mathew and Takagi 2001). The most important parameters of CaPO 4 are the ionic Ca/P ratio, basicity/acidity and solubility.…”
Section: The Members Of Capo 4 Familymentioning
confidence: 99%
See 1 more Smart Citation